Markers of JC virus infection in patients with multiple sclerosis under natalizumab therapy. Issue 1 (February 2015) - Clausi, Valeria; Giannecchini, Simone; Magnani, Eliana; Repice, Anna; Mechi, Claudia; Martelli, Francesco; Azzi, Alberta; Massacesi, Luca
Abstract : Objective: To evaluate the frequency of JC polyomavirus (JCPyV) infection and anti-JCPyV antibodies in patients with multiple sclerosis under natalizumab therapy. Methods: Presence of anti-JCPyV antibodies and JCPyV DNA was analyzed in 39 patients with relapsing-remitting multiple sclerosis undergoing natalizumab therapy. Anti-JCPyV antibodies were evaluated in serum by a 2-step virus-like particle-based ELISA assay (Stratify), and JCPyV DNA was evaluated in peripheral blood mononuclear cells, plasma, and urine by quantitative PCR. The anti-JCPyV antibodies were evaluated in serum samples collected at the same time or later than those collected for DNA analysis. Results: JCPyV DNA was detected in 59% of patients, and anti-JCPyV antibodies were present in 67%. JCPyV DNA occurred more often in blood than in urine. Anti-JCPyV antibodies were observed in 70% of the JCPyV-infected patients, and JCPyV DNA was detected in 50% of the patients without anti-JCPyV antibodies. When JCPyV DNA was investigated in blood and urine the frequency of infection was higher than previously described. Conclusion: Under these experimental conditions, with respect to the observed frequency of JCPyV infection, the sensitivity of the anti-JCPyV antibody assay was lower than expected.